AKTIVITAS EKSTRAK DAUN PIRDOT (Saurauia vulcani) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - eva lumban gaol; Ulfayani Mayasari (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2018)
Pirdot is a natural medicinal plant contains flavonoids that has antibacterial properties. The bacteria tested in this experiment is E. coli that causes of diarrhea. This study was to determine the antibacterial effect of pirdot leaves made in an extract preparation by the diffusion method using paper discs.. This study also used Tetracycline as a comparison, where this antibiotic is very sensitive to E. coli bacteria. Pirdot leaf extract was made in various concentrations, namely 12.5%, 15%, 17.5% and 20% and 20 mcg and 30 mcg of Tetracycline concentrations. The results showed that pirdot leaf extract in E. coli was able to inhibit with a concentration of 12.5% of 10.41 mm, 15% of 11.71 mm, 17.5% of 14.08%, and 20% of 15.43 mm, while the 20 mcg Tetracycline comparison was 18.73 mm and 20.71 mm at 30 mcg. So the conclussion from this research are the concentration of 12.5% and 15% can not be not said to be antibacterial but at concentrations of 17.5% and 20% can be said to be antibacterial. Keywords: Pirdot leaf, Eschericia coli, antibacterial.